Performansi Mesin Pendingin Tipe Chiller untuk Cold Storage dan Indoor Menggunakan Ethylene Glycol Coolant - Aziz, Azridjal; Syahputra, Hendrik; Mainil, Rahman Putra; Kurniawan, Afdhal (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2015)
Abstract Refrigeration device is used to reduce the temperature of the room or cooled material by absorbing heat from the room/material. The most refrigeration device operated by using the vapor compression refrigeration cycle. This research was done experimentally using refrigeration device chiller type to cool the ethylene glycol coolant in the refrigeration box (evaporator unit), and ethylene glycol coolant is used to absorb heat in cold storage and indoor (test room). The results show for the circulation of ethylene glycol coolant to the cold storage COP value is 2.80, while the circulation of ethylene glycol coolant to the indoor COP value is 5.12. On the testing of ethylene glycol coolant was circulated to the indoor with 1000 Watt cooling load, the COP value is 5.19, and for circulated to the cold storage and indoor simultaneously COP is of 3.66. The performance of chiller refrigeration device is influenced by the cooling load, the greater of cooling load that would affect the work of the compressor so that the pressure in compressor increase and the energy consumption to operate the compressor also increasing too. Keywords: refrigeration, heat, COP, PF, cooling load.